2015
DOI: 10.17795/dcej-4601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Oral Zinc Sulfate on Burning Mouth Syndrome: A Double Blind Randomized Clinical Trial

Abstract: Background: Burning Mouth Syndrome (BMS) is a common condition that affects menopausal women and patients experience a severe burning sensation in their mouth. So far there have been no definitive treatment for this disease. Objectives: The present study was undertaken to evaluate the efficacy of zinc supplement in improving the symptoms of burning mouth syndrome. Patients and Methods: Sixty patients were enrolled in this study; they were randomly divided to two groups. Patients in the intervention group recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…Approximately 60% of patients receiving radiotherapy develop oral mucositis and the incidence may increase up to 90% with concurrent chemotherapy (6). Symptoms such as a burning sensation and pain are due to loss and thinning of the mucosal epithelial barrier during the treatment, transforming into a painful, debilitating condition, depriving the patient of nutrition and oral care, and potentially acting as a source of infection (2,5,7,8).…”
mentioning
confidence: 99%
“…Approximately 60% of patients receiving radiotherapy develop oral mucositis and the incidence may increase up to 90% with concurrent chemotherapy (6). Symptoms such as a burning sensation and pain are due to loss and thinning of the mucosal epithelial barrier during the treatment, transforming into a painful, debilitating condition, depriving the patient of nutrition and oral care, and potentially acting as a source of infection (2,5,7,8).…”
mentioning
confidence: 99%
“…There was a single RCT assessing systemic zinc administration for the prevention of OM in patients receiving CT for solid and hematologic malignancies [21]. This study concluded zinc was ineffective.…”
Section: Zinc (Systemic): Hematologic and Solid Cancers Ct-preventiomentioning
confidence: 99%
“…Only one article in the sample analysed interventions involving zinc sulphate (Arbabi‐Kalati et al . ), amifostine (Stokman et al . ), chewing gum (Gandemer et al .…”
Section: Resultsmentioning
confidence: 99%
“…The WHO Oral Toxicity Scale (World Health Organization ) was the most commonly used and was adopted by 12 articles (Arbabi‐Kalati et al . , Pitten et al . , Stokman et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation